Exploring the exposure of Slovak banks' corporate loan portfolio to flood risk - Lea Gogová; Juraj Hledik; Ján Klacso (European Commission, 2025)
Climate change is expected to lead to more frequent and intense extreme weather events, such as floods and droughts, which in turn increase physical risks. In this paper, we assess the direct exposure of Slovak banks' corporate loan portfolios to riverine flood risk. We propose several monitoring metrics and estimate exposures at risk due to riverine flooding. Our analysis leverages a comprehensive dataset that integrates flood risk maps from the European Commission's Joint Research Centre, cadastral data on firm properties, credit register data, and firms' financial statements. While a significant share of firms are located in flood-prone areas, only a subset are likely to face flood levels that exceed critical thresholds. Consequently, the direct impact of riverine flooding on corporate credit risk appears to be relatively moderate - with the estimated increase of exposure at default ranging from 2 to 10 basis points of the corporate loan portfolio under standard scenarios, and up to 50-60 basis points in conservative stress cases accounting for asset value declines. Under counterfactual scenarios assuming a fivefold increase in the frequency of floods, the estimated increase exceeds 1 percentage point of the loan portfolio.
Keywords: G21; Q54; R30; 330; Riverine flood risk; credit risk; non-financial corporations; Slovaki